2013
DOI: 10.1111/ijs.12212
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Multimodal MRI in Transient Ischemic Attack

Abstract: Approximately three-quarter of transient ischemic attack is associated with multimodal magnetic resonance imaging abnormality. Initial perfusion-weighted imaging abnormality predicts newly developed diffusion-weighted imaging lesions, and symptomatic magnetic resonance angiogram abnormality seems to be the most important predictor for subsequent clinical events. Multimodal magnetic resonance imaging appears to be useful in assessing transient ischemic attack and predicting outcome in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In spite that our data were not as perfect as Dutta D study, however, our findings were consistent with it. It was reported that the AUC of ABCD2 score and ABCD3-I score was 0.50 and 0.58 in South Korea population [30]. In the population of Spain, the area under the ROC curve of ABCD2 and ABCD3-I for ischemic events prediction were 0.49 and 0.77 [31].…”
Section: Discussionmentioning
confidence: 96%
“…In spite that our data were not as perfect as Dutta D study, however, our findings were consistent with it. It was reported that the AUC of ABCD2 score and ABCD3-I score was 0.50 and 0.58 in South Korea population [30]. In the population of Spain, the area under the ROC curve of ABCD2 and ABCD3-I for ischemic events prediction were 0.49 and 0.77 [31].…”
Section: Discussionmentioning
confidence: 96%
“…With advances in MRI, up to three-quarters of TIAs defined by the traditional time-based definition have been found to have evidence of tissue damage. 19 This has sparked a shift towards use of a tissue-based definition of TIA. However, timely access to MRI and expert interpretation is not always available, and MRI is not cost-effective compared to CT. 20 It also remains to be seen whether use of plasminogen activator in patients with recent prior clinical symptoms lasting <24 hours associated with small MRI lesions is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the ethics committee of our center. For the prospective cohort we enrolled 162 consecutive TIA patients who visited Asan Medical Center (AMC) within 72 hours of symptom onset between July 2009 and December 2011 8. TIA was defined as a brief loss of brain function (lasting less than 24 hours) that was presumed to be due to cerebral ischemia.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed protocol and parameters of MRI have been described previously 8. The MRI images were assessed independently by two stroke neurologists who were blinded to clinical data, with discrepancies resolved by consensus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation